Development and validation of a time-motion judo combat model based on the Markovian Processes - Miarka, B.; Branco, B. H. M.; Vecchio, F. B. D.; Camey, S.; Franchini, E. (International Journal of Performance Analysis in Sport, 2015)
The aim of the study was to develop a technical-tactical model of judo combat. Thus, 2.316 combats performed by men ranked as the world's best and qualified for the 2012 Olympics Games were collected in 2011 and 2012, and 769 performances were used and 53.403 combat situations were analyzed. In order to develop the model of combat situations and the combinations between phases, as well as their respective components, the statistical analysis used the multi-state Markov Model. Moreover, the objectivity of the analysis was observed with comparisons and, the intra and inter-agreement was verified by means of the Cohen Kappa coefficient. Results showed no differences among analysts and referent to the actions in each phase of combat, the correlations analyses showed a "Almost perfect" classification for 87% of all variables analyzed. Regarding Markovian process analysis of the combat phases, results show the main tactical systems of attacks, where attack to the front follows attack to the right in the most part of the time and the highest likelihood to occur a projection is after attack to the front and to the right orientations. This information can help analysts and coaches to improve tactical and physiological athlete's performance.